2 câu trả lời
Đáp án:
Giải thích các bước giải:
$-x^2-x+2>0\\⇔x^2+x-2<0\\⇔(x-1)(x+2)<0\\⇔\begin{cases} x-1<0\\x+2>0\end{cases}\\⇔\left[\begin{matrix} \begin{cases} x-1<0\\x+2>0\end{cases}\\ \begin{cases} x-1>0\\x+2>0\end{cases}\end{matrix}\right.\\⇔\left[\begin{matrix} \begin{cases} x<1\\x>-2\end{cases}(L)\\ \begin{cases} x>1\\x<-2\end{cases}(N)\end{matrix}\right.\\⇔-2<x<1$
`#Ken`
Đáp án+Giải thích các bước giải:
$-x^{2}$ - x + 2 > 0
$\Leftrightarrow$ (x - 1)(x + 2) > 0
Đặt f(x) = (x -1)(x + 2)
$\Leftrightarrow$ \(\left[ \begin{array}{l}x - 1 = 0\\x+2=0\end{array} \right.\)
$\Leftrightarrow$ \(\left[ \begin{array}{l}x=1\\x=-2\end{array} \right.\)
BXD
x âm vô cùng -2 1 dương vô cùng
x -1 - | - 0 +
x + 2 - 0 + | +
f(x) + 0 - 0 +
Vậy tập nghiệm của phương trình là S = [-2;1]